Widely Targeted Metabolomics Reveals Metabolic Divergence in Abutilon theophrasti Populations Under Glufosinate Ammonium Treatment - Xiaotong Guo; Yu Wang; Yulian Guo; Chan Luo; Keqiang Cong (Plants, 2025)
Abutilon theophrasti Medikus, a pervasive weed infesting transgenic corn fields, exhibits increasing tolerance to glufosinate ammonium—a widely used herbicide in genetically modified cropping systems. This study employed a widely targeted metabolomics approach to investigate differential metabolic responses to glufosinate ammonium across two Abutilon theophrasti populations under identical treatments. A total of 2546 metabolites were detected, predominantly classified into alkaloids, amino acids and derivatives, and flavonoids, among other categories. Three pivotal metabolic pathways (Arginine and proline metabolism, Biosynthesis of amino acids, D-amino acid metabolism) were identified as critical regulators of herbicide response. These findings advance our understanding of weed metabolic adaptation to glufosinate ammonium and lay a foundation for elucidating potential herbicide resistance mechanisms in weeds.